Minimizing the Adhesion Effects in Food Packages Forming by the Use of Advanced Coatings - Fernandes, L. (2020)
The metal packaging industry used for food application has undergone drastic changes in the demands of its final consumers. The raw material for these packages, is a low carbon steel coated with a thin layer of tin (2,0 g/m2), also known as tinplate. The stamping process of these packages occurs at room temperature and is critically influenced by the tin transfer from the steel surface to the tool surface, mainly due to the tin softness. This problem is easily solved using lubrification but the purpose of this study will be the reduction or even absence of lubricants during the process in order to comply with costumers’ requirements. A successful way to minimize the consumption of lubricants is to use tools which are coated with PVD (Physical Vapour Deposition) advanced coatings deposited with unbalanced magnetron sputtering technique. Thin WC (Tungsten Carbide) and CrCN (Chromium Carbonitride) coatings were deposited using PVD on tool stamping steel – AISI D2. Block on ring tribological tests were performed on the coatings against tinplate counterface in order to investigate their wear performance, with particular emphasis on the material transfer (tin) phenomena during the sliding tests. The results allowed for selecting the best coating tested with a view to avoid the tin adhesion to the die.